Religious Nicknames in Aramaic Dialects - Amer Aboud, Omar (Opción, 2019)
The study of Religious nicknames in the Aramaic dialects is an important subject for understanding the similarities and linguistic differences in their vocabulary, as well as their influence and influence in many languages of the former and contemporary peoples, including the Akkadian language in its Babylonian and Assyrian dialect, especially as it became the language of diplomacy in the ancient Near East in the second half From the first millen- nium BC, because of its 22-letter alphabetic characters, as well as the ease of writing them on boards and animal skins. The Aramaic language belongs to the northwestern part of a group of Semi- tic languages spoken by the Aramaic peoples that inhabited the ancient Syria and the Mesopotamia. As a result of its spread, friction and length of time, two groups of Oriental dialects appeared, including the Babylonian Aramaic dialect, The Syriac dialect, the dialect of Mandaean, the urban dialect and the dialect of the Sorath. The Western group includes the Samaritan dialect, the Palestinian Aramaic dialect, the Palestinian Christian Aramaic dialect, the destructive dialect and the Nabatean dialect. The aim of the research is to shed light on the linguistic aspect, as well as the organizational and administrative aspects of the Aramaic religious establish- ment, since any religious system necessitates the existence of an institution that supervises and directs this system. The priests have different degrees, ranks and functions. And the supervisors of the various religious rituals of prayer, offerings, hymns, playing, predicting and various religious obser- vances have been followed in the writing of this research analytical and comparative method, and contained the search on a series of Religious nick- names in alphabetical order as well as the introduction and conclusion